Digital Behavior Analysis and Decoding Marketing Merits of Top Indian Institutes - Agrawal, Mitalee (Journal of Digital Marketing and Communication, 2024)
The impact of social media on higher education institutions is extensive, making it a crucial focus for studying the role of social media marketing in education. In India, the National Institutional Ranking Framework (NIRF) plays a pivotal role in assessing the position of higher education institutes, categorized as public/private and technical/non-technical. NIRF 2022 ranked 1,350 institutes, considering parameters such as academics, research, innovation, financials, graduate outcomes, inclusivity, and perception. While perception holds a 10% weight, it significantly influences other primary parameters. Post-COVID and thanks to rapid digitalization, there has been a significant surge in social media usage by the youth of the country. Consequently, social media has emerged as a prime source of communication for educational institutes as well. This study focuses on analyzing "Digital Marketing Strategies," referred to as "Digital Behaviour," by examining Twitter usage among the top 50 institutes in the NIRF 2022 overall category in India. It also suggests a reference model, FACHIO©, for digital marketing by higher education institutions, which can be followed by institutes abroad. The conclusion discusses how FACHIO© can play a pivotal role in the era of digital marketing in higher education. The basic idea can be utilized to make comparative analyses and develop suitable strategies for digital marketing in other sectors as well.